O estatuto epistemológico do conceito de ideologia científica segundo Georges Canguilhem - Silva, Fabrina Moreira (2011)
Given the intention of bringing together Canguilhem Epistemology and History of Science, as a methodological alternative in the face of scientific programs of contemporary historiography, the objective of this work that led to the formulation of the concept of scientific ideology (1969), just to meet deficiencies identified by the epistemologist present practice of contemporary historians of Science. The Canguilhem's epistemological project is to give the story a philosophical aspect of science, or an aspect of coping with difficulties which concern relations between false and true or apparent, of the respective statutes of truth and error. This work constitutes in the investigation of historical and epistemological intricacies Canguilhem that led to the proposal of your project within the epistemological scientific historiography. The goal is not simply to provide historical basis for the exhibition, but to indicate, through the details of your project, the epistemological status of scientific concept of ideology. It is determined, the study of three methodological texts of Georges Canguilhem, not so much imposed as a figure of academic knowledge, but especially as an expression of constant reflection: The object of the history of science (1966), What is a scientific ideology? (1969) The role of epistemology and historiography in contemporary science (1970). These texts indicate gathered in a way, the range of his philosophical reflections in the field of scientific historiography. Three studies on the characterization of the ontological sense, the theme of history of science in setting up the life sciences. Canguilhem reacts in these three studies, as directed against an order historiographical sprayed from a positivist philosophy of history in the tradition of A. Comte. Nutshell, the epistemological assumption that governs the history of positivist science Canguilhem second is "the chronological precedence is a logical inferiority." That is, the history of science is just an injection of life in the exhibition of scientific results. The major problem faced by Canguilhem forward to this aphorism history - which seeks to know which way the continuity can be established and for many different spirits and successive one single horizon - is no longer the tradition and the trail, but the cut and limit. The change of perspective of tradition and to trace and cut out containing an inversion in the way of doing history of science, which implies a change of object and method. The history of science should be the descriptive analysis and the theory of different transformations that serve as the foundation of the scientific foundations and renewal, and so should therefore take care of the epistemological issues concerning science, the historian is willing to talk. Schematically, the scope of this paper is to point out that: (i) the concept of scientific ideology is closely linked to the epistemological problem concerning the permanent constitution of scientific knowledge, (ii) the entanglement between ideology and science to prevent the reduction of history science to the monotony of a frame without a shadow of relief, and the separation between science and ideology must keep themselves as continuing in the history of science that seems to have preserved elements of an ideology